Fear, stress and resilience in nursing students about their return to hospital practices, post health emergency in a private university, Juliaca - Mamani Limachi, Rut (2023)
Objective: To determine the relationship between fear, stress and resilience in nursing students on their return to hospital practices, post health emergency in a private university, Juliaca, 2022. Methods: Quantitative approach, cross-sectional multiple correlational type; as well as it has a non-experimental design. A total of 300 nursing students from third to seventh cycle participated. Regarding the analysis, the descriptive analysis was performed with measures of central tendency, while the inferential one with Spearman’s Rho correlation. Results: The correlation analyzes determined that there is a relationship between the variables (p<0.05), as well as low levels of fear (60.3%), means of stress (71%) and means of resilience (54.3%). Conclusions: Resilience is supposed to be an important factor and is negatively related to stress and fear, so high levels of resilience would allow low levels of fear and stress.